CRIMINAL LIABILITY PERPETRATOR Bullying THROUGH SOCIAL MEDIA - Wijaya, Junika Nurhamidah; Johardi, Ali; Pratiwi, Siswantari (JILPR Journal Indonesia Law and Policy Review, 2024)
The elements of the object of a criminal offense are acts carried out by distributing and/or transmitting and/or making accessible electronic information and/or electronic documents. The elements of criminal liability for perpetrators of criminal acts of cyber bullying must fulfill the elements regulated in Article 27 paragraph (3) of the ITE Law. Even though the highest criminal threat for cyber bullying is only four years in prison, the consequences of this act are very detrimental to the victim, both material and immaterial losses. The crime of cyber bullying can be seen as a result of relatively weak legal consequences or legal instruments. The problem faced is what kind of consequences are experienced by people who have become victims of cyber bullying. In Supreme Court Decision Number 120/Pid.Sus/2017/PN Lbo and Supreme Court Decision Number 95/Pid.Sus/2020/PT Gto, what is the criminal responsibility for those who carry out bullying behavior via social media? A normative legal research approach is used in this research. In conclusion, the impacts experienced by victims of cyber bullying include feeling hurt and afraid, often blaming themselves for the events they experienced, self-harm , experiencing sadness, and even thoughts and intentions to commit suicide. Criminal Responsibility of Perpetrators of Bullying Through Social Media in the Supreme Court Decision Number 120/Pid.Sus/2017/PN Lbo and Supreme Court Decision Number 95/Pid.Sus/2020/PT Gto the defendant of the crime of cyber bullying fulfills the element of responsibility as a subjective element, the defendant able to take responsibility for his actions, and the defendant does not have mental disorders or mental illness according to the Supreme Court decision.